Atom‐Resolved Investigation on Dynamic Nucleation and Growth of Platinum Nanocrystals. Issue 6 (24th March 2022) - Ye, Huanyu; Yang, Feng; Sun, Yinghui; Wang, Rongming
Abstract: Understanding the mechanism of nucleation and growth of nanocrystals is crucial for designing and regulating the structure and properties of nanocrystals. However, the process from molecules to nanocrystals remains unclear because of the rapid and complicated dynamics of evolution under reaction conditions. Here, the complete evolution process of solid‐phase chloroplatinic acid during the electron beam irradiation triggered reduction and nucleation of platinum nanocrystals is recorded. Aberration‐corrected environmental transmission electron microscopy is used for direct visualization of the dynamic evolution from H2 PtCl6 to Pt nanocrystals at the atomic scale, including the formation and growth of amorphous clusters, crystallization, and growth of clusters, and the ripening of Pt nanocrystals. At the first two stages, there exists a critical size of ≈2.0 nm, which represents the start of crystallization. Crystallization from the center and density fluctuation are observed in the second stage of the crystallization of a few clusters with a size obviously larger than the critical size. The work provides valuable information to understand the kinetics of the early stage of nanocrystal nucleation and crystallization at atomic scale. Abstract : The dynamic nucleation and growth mechanism of platinum nanocrystals in solid‐phase are investigated by in situ methods. Three stages including the formation of the amorphous cluster, crystallization, and ripening are resolved at high spatial and temporal resolution. Critical size of 2.0 nm of clusters is found for initiating the crystallization stage. This method shall provide a deeper understanding of the solid‐phase nucleation mechanism.